2019
DOI: 10.1016/j.cub.2019.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Causal Evidence for Expression of Perceptual Expectations in Category-Selective Extrastriate Regions

Abstract: Highlights d Expectations influence perception of visual events d Anticipatory activity in category-specific regions expresses expectations d Disruption of this activity removes effects of cues on discrimination performance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 55 publications
(59 reference statements)
4
34
0
Order By: Relevance
“…John-Saaltink et al, 2016). This finding is in line with previous work suggesting the prestimulus state of the sensory cortex biases perception (Gandolfo and Downing, 2019; Kok et al, 2017; Sherman et al, 2016; Hesselmann et al, 2008; Pajani et al, 2015; Han and VanRullen, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…John-Saaltink et al, 2016). This finding is in line with previous work suggesting the prestimulus state of the sensory cortex biases perception (Gandolfo and Downing, 2019; Kok et al, 2017; Sherman et al, 2016; Hesselmann et al, 2008; Pajani et al, 2015; Han and VanRullen, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Like outlined in Bayesian accounts, perception is first biased towards prior knowledge to aid rapid generation of largely accurate perceptual experiences. This process may be operational from the point at which predictions can be made, through pre-activation of expected units [1,48,49]. However, when an event generates high surprise -as would be the case only for highly 'unexpected' events (see below)…”
Section: A Theoretical Resolutionmentioning
confidence: 99%
“…Evidence for such a mechanism has been provided by a number of neuroimaging techniques. For instance, transcranial magnetic stimulation demonstrates that disruptive pulses to sensory regions at the time of predictive cues eliminates perceptual cueing effects (Gandolfo & Downing, 2019), magnetoencephalography work demonstrates that visual events can be decoded from visual brain activity before they are presented (Kok et al, 2017), and functional magnetic resonance imaging studies indicate that sensory suppression is observed only in voxels that do not encode the presented stimuli (Kok et al, 2012;. Such predictive neural 'sharpening' processes are thought to upweight, rather than downweight, perception of expected events, enabling rapid generation of largely veridical experiences in the face of sensory noise Kersten et al, 2004;Yuille & Kersten, 2006).…”
Section: Introductionmentioning
confidence: 99%